Analisis Pendapatan Pengrajin Sarung Tenun di Desa Katukobari Kabupaten Buton Tengah - Rasnawati, Rasnawati; Kartomo, Kartomo; Syaiful, Muhammad (Journal of Geographical Sciences and Education, 2024)
The existence of small industries has a significant influence on the economic development of a country. This research was conducted to analyze the income of woven sarong craftsmen and the feasibility of the woven sarong business in Katukobari Village, Central Buton Regency. This study uses a quantitative descriptive approach where data was obtained through observation and interviews, then analyzed using the income calculation method, Net R/C Ratio, and Break Event Point (BEP). The research results show that the average production of craftsmen reaches 3 units with a selling price per unit of Rp. 176,900, wich results in total receipts of Rp. 531,000. After deducting the total cost of Rp. 336,873, the net income obtained was Rp. 192,924. The R/C Ratio is 1.5 and the production BEP is 1.90 and the price BEP is Rp. 112,291 shows that the woven sarong business in Katukobari Village is financially feasible to develop. In conclusion, this business has good prospects for further development in the area.